Changes in Bone Mineral Density May Predict the Risk of Fracture Differently in Older Adults According to Fall History. Issue 12 (29th November 2014) - Berry, Sarah D.; McLean, Robert R.; Hannan, Marian T.; Cupples, L. Adrienne; Kiel, Douglas P.
<x xml:space="preserve">Abstract</x> Objectives To determine whether the association between change in bone mass density (BMD) over 4 years and risk of hip and nonvertebral fracture differs according to an individual's history of falls. Design Population‐based cohort study. Setting Framingham, Massachusetts. Participants Individuals with two measures of BMD at the femoral neck (mean age 78.8; 310 male, 492 female). Measurements Cox proportional hazards models were used to estimate hazard ratios (HRs) for the association between percentage change in BMD (per sex‐specific standard deviation) and risk of incident hip and nonvertebral fracture. Models were stratified based on history of falls (≥1 falls in the past year) and recurrent falls (≥2 falls) ascertained at the time of the second BMD test. Interactions were tested by including the term "fall history * change in BMD" in the models. Results Mean change in BMD was −0.6%/year; 27.8% of participants reported falls, and 10.8% reported recurrent falls. Seventy‐six incident hip and 175 incident nonvertebral fractures occurred over a median follow‐up of 9.0 years. There was no difference in the association between change in BMD and hip fracture according to history of falls (P for interaction = .57). The HR associated with change in BMD and nonvertebral fracture was 1.31 (95% confidence interval (CI) = 1.10–1.56) in participants without a history of falls and 0.95 (95% CI 0.70–1.28) in those with a fall (interaction P = .07). Results for recurrent fallers were similar. Conclusion The effect of BMD loss on risk of nonvertebral fracture may be greater in persons without a history of falls. It is possible that change in BMD contributes less to fracture risk when a strong risk factor for fracture, such as falls, is present.